Volumetric properties and viscosity for the ternary system of (1-pentanol + ethylcyclohexane + methyl myristate) and corresponding binary systems at T = 293.15–323.15 K. (February 2022) - Li, Dan; Zheng, Yujia; Wang, Jingying; Pang, Yan; Liu, Meifang
Graphical abstract: Highlights: Density and viscosity of a ternary system (1-pentanol + ethylcyclohexane + methyl myristate) were investigated. V E and Δ η of the ternary mixtures were calculated and fitted to Cibulka and Redlich–Kister equation. The change of V E and Δ η is mainly due to the change of intermolecular hydrogen bond. Abstract: Densities and viscosities of ternary system (1-pentanol + ethylcyclohexane + methyl myristate) and the corresponding binary systems, (1-pentanol + ethylcyclohexane), (1-pentanol + methyl myristate), and (ethylcyclohexane + methyl myristate) were determined at different temperatures from 293.15 to 323.15 K. The experimental data were further employed to calculate excess molar volume ( V m E ) and viscosity deviation (Δ η ). Over the whole composition range, the V m E values show positive deviations from ideal behavior and the Δ η values are negative. The V m E values for the ternary mixtures were also correlated with the corresponding binary data using Cibulka and Redlich–Kister equations, respectively. The experimental data and results provide useful base data for further thermodynamic studies of alcohol–biodiesel–diesel blends.